Highly efficient, low-temperature hydrogen release from perhydro-benzyltoluene using reactive distillation - Geißelbrecht, Michael; Mrusek, Stephan; Mueller, K.; Preuster, P.; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2020)
The need to supply significant amounts of heat at the high temperature level required thermodynamically for cycloalkane dehydrogenation has so far been seen as the main hurdle to bring the otherwise highly attractive Liquid Organic Hydrogen Carrier (LOHC) technology to broad technical use. The LOHC technology promises infrastructure-compatible storage and transport of hydrogen in chemically bound form,e.g.for long-term energy storage, global energy logistics and heavy-duty mobility. Our contribution shows that hydrogen release from the hetero-atom free, pure hydrocarbon LOHC compound perhydro-benzyl toluene is possible at temperatures down to 200 degrees C, if the operation is carried out in a reactive distillation column under reduced pressure. Such low temperature dehydrogenation of hydrocarbon-based LOHC systems facilitates heat integration with waste heat sources and the energetic use of the released hydrogen considerably, and this will greatly enhance the attractiveness of LOHC-based hydrogen storage for many applications.
CRIS-Team WoS Importer:2020-10-02

Hydrogen extraction from methane-hydrogen mixtures from the natural gas grid by means of electrochemical hydrogen separation and compression - Mrusek, Stephan; Blasius, Marco; Morgenroth, Frank; Thiele, Simon; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
One interesting option to store and transport hydrogen in the future is to blend it into the natural gas grid. In this paper, we present technological insights regarding electrochemical hydrogen separation and compression (EHC/S), a technology that enables extraction of compressed and purified hydrogen from such blends. Our contribution discusses two use cases, namely i) hydrogen separation to recover purified hydrogen under pressure, and ii) hydrogen removal to protect downstream methane consumers from excessive hydrogen levels. Our experimental work with a laboratory scale EHC/S centers on efficiency aspects. We show that at low hydrogen contents in dry feed gas, gas humidification causes relevant thermal energy consumption, that cannot be provided by EHC/S waste heat. We also show that hydrogen recovery is restricted by mass transport if the residence time in the EHC device is too short. Simultaneous hydrogen separation and compression from 5% hydrogen in methane is demonstrated yielding hydrogen at 6 bara at the cathode.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Electrochemical hydrogen compression; Electrochemical hydrogen separation; Hydrogen purification; Hydrogen storage; Natural gas grid

Pressurized hydrogen from charged liquid organic hydrogen carrier systems by electrochemical hydrogen compression - Mrusek, Stephan; Preuster, Patrick; Müller, Karsten; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
We demonstrate that the combination of hydrogen release from a Liquid Organic Hydrogen Carrier (LOHC) system with electrochemical hydrogen compression (EHC) provides three decisive advantages over the state-of-the-art hydrogen provision from such storage system: a) The EHC device produces reduced hydrogen pressure on its suction side connected to the LOHC dehydrogenation unit, thus shifting the thermodynamic equilibrium towards dehydrogenation and accelerating the hydrogen release; b) the EHC device compresses the hydrogen released from the carrier system thus producing high value compressed hydrogen; c) the EHC process is selective for proton transport and thus the process purifies hydrogen from impurities, such as traces of methane. We demonstrate this combination for the production of compressed hydrogen (absolute pressure of 6 bar) from perhydro dibenzyltoluene at dehydrogenation temperatures down to 240 °C in a quality suitable for fuel cell operation, e.g. in a fuel cell vehicle. The presented technology may be highly attractive for providing compressed hydrogen at future hydrogen filling stations that receive and store hydrogen in a LOHC-bound manner.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Compression; Dehydrogenation; Heat integration; Hydrogen storage; Purity